Random Access Preambles for Evolved UTRA Cellular System - Popovic, B.M.; Mauritz, O. (2006 IEEE Ninth International Symposium on Spread Spectrum Techniques and Applications, 2006)
The design of random access channel (RACH) preambles for the evolved universal terrestrial radio access (E-UTRA) third generation cellular system is considered, with the major goal to minimize the latency of RACH procedure. The E-UTRA RACH preambles are designed starting from a new construction of the sets of zero correlation zone (ZCZ) sequences, derived from the generalized chirp-like (GCL) sequences